The importance of selective collection for local sustainable development: Historic rescue in Olinda/PE (Research, Society and Development, 2022)
The objective of the study was to carry out a socio-evolutionary analysis of the selective collection program in the municipality of Olinda, from its implementation to the present day. The methodology used is configured as a case study, including qualitative and quantitative approaches, through a historical survey of documents and laws, in addition to semi-structured questionnaires to identify the socioeconomic level of recyclable material collectors. In view of the social, environmental and economic problems that the municipality of Olinda has been facing, mainly the difficulties regarding the management and operation of urban solid waste in a city considered cultural heritage, as the research brings the problem of paradigm shifts. Obstacles were found in the program, namely: Lack of management and planning, lack of public policies and little technical and administrative skills. At the same time, we sought to contribute to the municipal management in decisions to invest in public policies aimed at selective collection in a more systematic way. Municipal management does not have an adequate structure for the provision of selective collection service to serve the population.